Pandangan Alkitab Terhadap Penderitaan Orang Kristen (Eksposisi Wahyu 2:8-11) - Depparua, Agustinus (Sekolah Tinggi Teologi Injili Indonesia Palu, 2023)
The condition of poverty is often considered by some people as a curse or at least as a consequence of a lack of faith in a Christian. This is frequently understood by adherents of prosperity theology. On the other hand, there are groups that believe if someone has not experienced suffering, then their faith is still questionable. This view is commonly expressed by adherents of the theology of suffering. Is this what the truth of God's Word teaches? This article will discuss the topic of suffering in the perspective of the Bible, especially in Revelation 2:8-11.